Facilităţile bazelor de date oferite prin Proiectul Internaţional MDRONO pentru cercetarea universitară [Articol] - Dascal, Olga; Zadainova, Snejana (BŞ USARB, 2024)
The activity of the Bălţi university library is focused on the accomplishment of the most important mission - informational and documentary provision of the study and research processes, oﬀering the widest possible spectrum. Within the Project ,,Modernization of the services of university libraries in the Republic of Moldova”, access to scientiﬁc databases was ensured: Web of Science, Cambridge Journals Online, SAGE Research Methods, Taylor & Francis Online Journal Library.
Database facilities provided by the MDRONO International Project for university research
Keywords: international project; information; databases; modern services; information resources and services; information culture; dissemination; promotion; training